Legalitas Anggota TNI Aktif Dalam Rangkap Jabatan Sipil: Studi Terhadap Undang-Undang Nomor 34 Tahun 2004 Tentang Tentara Nasional Indonesia - Muhammad Adlan Kamil; A Salman Maggalatung; Feni Arifiani (JOURNAL of LEGAL RESEARCH, 2022)
The question of active TNI members holding civilian positions has sparked much controversy. The TNI's right to shape Indonesia's future, the accumulation of non-job TNI officers, and the government's direct policy of asking active TNI members to choose civilian jobs were cited as major factors. To explain the role, status, and function of Indonesia's TNI in the country's constitutional system and the legality of TNI personnel working in parallel civilian occupations. This study use the statute technique for formative and library research. This approach to legislation references Law 34 of 2004 on the Indonesian National Army and TAP MPR Number VII/MPR/2000 on the role of the TNI and POLRI. The study's legal experts' doctrine or theory is called the conceptual approach. This research found that many civilian positions held by active TNI members are illegal. State Security, Presidential Military Secretary, State Intelligence; National Code; National Defence Institutions; and the National Defence Council are the only TNI disciplines that allow concurrent TNI positions. SAR. and the Supreme Court are not included. Many TNI members currently work in jobs that do not fit this description.